(untitled) (Pakistan Journal of Engineering, Technology and Science, 2025)
Distributed Generators (DGs) are extensively used as Distributed Energy Resources (DERs) and are now an integral part of modern distribution systems. Although these DGs improve the voltage profile and reduce power losses, they have introduced challenges such as islanding and safety issues. This article proposes the algorithm for the islanding detection and control of Voltage Source Converters (VSCs) based on Combined Voltage and Frequency Relays (CVFRs). The CVFR control structure is designed to identify the presence of islanding with minimum detection time and has a capability to change the mode of operation of VSC to provide a stable voltage supply to the connected load. The effectiveness of the proposed algorithm has been studied on the CIGRE LV Test Network with six sets of DGs using passive detection technique. The performance of the algorithm has been tested in a number of scenarios with simulation and comparison made with other detection techniques to validate the model. The system has been modeled and simulated using the software MATLAB/Simulink.